Evidence of pronounced electronic coupling in a directly bonded fullerene-ferrocene dyad - Hauke, Frank; Hirsch, Andreas; Liu, Sheng-Gao; Echegoyen, Luis; Swartz, Angela; Luo, Chuping; Guldi, Dirk Michael (ChemPhysChem, 2002)
A new donor-acceptor dyad (7) involving a ferrocene moiety as donor and an azafullerene as acceptor has been synthesized by treating bisazafullerenyl (1) with ferrocenium hexafluorophosphate. This compound represents the first example of a fullerene-based dyad where two electroactive groups are connected by only a single σ-bond. The cyclic voltammetry of 7, in comparison to the corresponding reference systems, clearly reveals strong electronic coupling between the ferrocene and the azafullerene moiety in the ground state. For example, the Fc-based, reversible, one electron oxidation wave is significantly positively shifted by 183 mV with respect to that of the parent ferrocene. This indicates the existence of intramolecular charge transfer (ICT) from the donating Fc to the accepting azafullerenyl group. Photophysical studies on 7 were carried out by means of emission and transient absorption spectroscopy. An instantaneous deactivation of the fullerene singlet excited-state results in the formation of the chargeseparated (CN)-(Fc) radical pair. From the charge-transfer dynamics with a lower limit of ≥ 5 × 10 s, we infer strong electronic coupling (V) between the azafullerene and the ferrocene moiety of the order of 60 cm in benzonitrile.